Electrical conductivity and interlaminar shear strength enhancement of carbon fiber reinforced polymers through synergetic effect between graphene oxide and polyaniline. (November 2016) - Cheng, Xiuyan; Yokozeki, Tomohiro; Wu, Lixin; Wang, Haopeng; Zhang, JinMeng; Koyanagi, Jun; Weng, Zixiang; Sun, Qingfu
Abstract: Utilizing synergetic effect of different ingredients is an important strategy to design new multi-functional composites. In this work, high-strength graphene oxide and conductive polyaniline were selected to dope into divinylbenzene to fabricate a new type carbon fiber reinforced polymer laminates, where a cooperative improvement of through-thickness electrical conductivity and interlaminar shear strength was observed. With addition of 15 wt% of PANI-GO at the optimized weight ratio of 60:1 in the CF/DVB-PANI-GO, 150% enhancement of the electrical conductivity compared to the CF/DVB-PANI, and 76% enhancement of the ILSS compared to the CF/DVB-GO were realized. Our laminates reach 66% in ILSS of that for the conventional CFRP made of epoxy, but the former features about 103 times higher AC conductivity. The mechanism for such a synergic enhancement for both electrical and mechanical performance was investigated by rheology measurement and scanning electron microscopy, where uniform 3-D network formed by PANI/GO has been clearly observed.